UPAYA PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMP MELALUI MODEL PROBLEM BASED LEARNING - Fathiyah Adlina Amelia; Kartini; Rini Dian Anggraini (Universitas Teknokrat Indonesia, 2026)
Mathematical problem-solving skills (MPS) are one of the key competencies in mathematics education because they relate to students’ ability to solve contextual problems in everyday life. This study aims to improve the learning process and enhance students’ MPS through the implementation of the Problem-Based Learning (PBL) model. This study employs the Classroom Action Research (CAR) method, conducted in two cycles during the odd semester of the 2025/2026 academic year. The research subjects were 26 eighth-grade students from Class VIII.2 at State Junior High School 5 Tambang. Each cycle consisted of the planning, implementation, observation, and reflection stages. Data collection techniques were carried out through PBL proficiency tests in the form of essay questions as well as observation sheets of teacher and student activities. The research results showed an increase in the average PBL proficiency score of students, namely from 26.91 on the initial test to 55.66 in cycle I, and increased to 67.79 in cycle II. These findings indicate that the implementation of the PBL model is effective in improving the quality of the learning process as well as students’ mathematical problem-solving skills. The novelty of this study lies in the correlation between each PBL syntax and the indicators of mathematical problem-solving skills in the material on linear equations and inequalities with one variable in class VIII.2 at SMP Negeri 5 Tambang.